Research on drought stress in Medicago sativa L. from 1998 to 2023: a bibliometric analysis - Zhou, Zijun; Li, Junqin; Gao, Yang; Wang, Xiangtao; Wang, Rui; Huang, Haiyan; Zhang, Yu; Zhao, Lili; Wang, Puchang (Frontiers in Plant Science, 2024)
Alfalfa (Medicago sativa L.) is one of the most important forage crops in the world. Drought is recognized as a major challenge limiting alfalfa production and threatening food security. Although some literature reviews have been conducted in this area, bibliometric reviews based on large amounts of published data are still lacking. In this paper, a bibliometric analysis of alfalfa drought stress from 1998–2023 was conducted using the Web of Science Core Collection database in order to assess global trends in alfalfa drought stress research and to provide new directions for future research. The results showed that the annual publication output maintained an increase in most years, with China and the United States contributing significantly to the field. Most of the journals published are specialized journals in botany, environmental science, soil science and crop science, as well as related agribusiness journals. “plant growth” and “yield” were the most frequently used keywords, reflecting the important purpose of research in this field. And two main research directions were identified: research on drought response mechanism of alfalfa and exploration of drought-resistant technology. In addition, physiological, biochemical, and molecular responses of drought tolerance and high yield in alfalfa, transgenics, and microbial fertilizer research have been hot research topics in recent years and may continue in the future. The ultimate goal of this paper is to provide a foundational reference for future research on alfalfa’s drought resistance and yield optimization mechanisms, thereby enhancing the crop’s application in agricultural production.